VICTIMOLOGY AND ITS APPLICATION IN INDIAN COURTS: STUDY BASED ON WORKING OF DISTRICT COURTS, PANIPAT (HARYANA) (Journal of Forensic Medicine & Toxicology, 2022)
Background: The legal offender justice system of India is a unique blend of the ancient Indian and British Indian laws along with the suitable amendments made for the dynamically evolving Indian subcontinent. However, the principles regarding the functioning of the offender justice system have practically remained constant for the past decades thereby, not uplifting the status of victims from being merely a witness for themselves and often ignoring their plight. Aim: The study was conducted with an objective to understand the practical Offender justice system in relation to the perspective of lawyers and the victims’ rights, problems and the plight faced by them. The study also emphasises on the exigency for the introduction of victimology and its experts in the picture. Methods: This study was based on analytical and descriptive secondary information and data, personally visiting the District courts, Panipat, Haryana under a senior lawyer, and interviewing attorneys, police personnel and victims of various crimes. A survey study of 55 lawyers was conducted to determine their perspectives on victim issues and the functioning of the judicial system in which they practise. Result: The data and interviews yielded that majority of the victims were frightened, nervous and panic-stricken at the thought of being involved in a court case. With an average rating of 5 (on a scale of 10), most lawyers had a modest impression of corruption in the judiciary and prosecution councils; nevertheless, the observation of the same for police personals was high, with 78 percent of lawyers agreeing that usually, the victims are demanded for money and bribe by the policemen. 62.5 per cent of victims had no practical information about the trial process while 55 per cent of victims showed panicked and stressed behaviour. 65 per cent of lawyers had information about the branch of victimology and 76 per cent of lawyers feel the need of having a professional victimologist at the ground level. Conclusion: This study puts forward that despite of several provisions and guidelines that are present for victims’ rights, very few show their practical application at the ground level. Thus, there is an exigency for amendments in the Indian Offender justice system in a manner that the justice providing entities become more sensitized and ‘Victim-Oriented’. There is an exigency that enough professional counsellors and psychologists are readily available so that the victims comprehend the procedure, and courtroom conduct and be mentally prepared to face the trial. The introduction of Victimology and its experts in the picture would be a fruitful step toward victims’ betterment and restoring their trust in the justice system.
Keywords: Victimology; Victim; Lawyers; Indian courts; Haryana